Doença do disco intervertebral Hansen tipo II em cães: fisiopatologia, abordagem clínico-cirúrgica e controvérsias - Tertuliano Marinho, Paulo Vinicius (2014)
Protrusion of the intervertebral disc can cause chronic progressive compression of the spinal cord, and the neurological associated signs vary according to anatomical location, duration and dynamic force of compression. The type II disc disease is not fully understood, and there are many controversies about is clinical significance and best form of treatment. The most important aspect of conservative treatment is rest and physiotherapy associated with mild exercise, and use of corticosteroids to reduce vasogenic edema. The spinal decompression by surgery for removal of disc material from within the medullary canal is the surgical treatment of choice in type I disc disease, but has technical limitations in the type II disc disease. The purpose of this paper is to review the pathophysiology and treatment of chronic intervertebral disc disease and discuss the controversies in medical treatment and the use of some traditional and new surgical techniques.